Edukasi Gizi Seimbang dan Pengelolaan Obat untuk Masyarakat Sehat Di Desa Tanjung Laimeu - Muhammad, Rajab; Rania, Rania Fatrizza Pritami; Sultan, Sultan Andilah; Harun, Marheni Fadilah; Fitri, Fitri Kurniawati; Munsir, Noviani Munsir; Tawakal, Tawakal; Lisnawati; Fajar Kurniawan; Nasrun, Efa Kelya Nasrun; Hasiu, Teti Susliyanti Hasiu (Nuban Jaggadhita Center, 2024)
This study aimed to improve community knowledge about balanced nutrition and medication management through educational interventions conducted on July 7, 2024, with 30 participants from Tanjung Laimeu village. The methods used included interactive lectures, direct demonstrations, and visual media such as posters and brochures. A pre-experimental design with pre-test and post-test measurements assessed knowledge before and after the intervention. The results showed a significant increase in participants' knowledge, with the average score rising from 19.75 to 26.10 and the standard deviation decreasing from 4.100 to 3.700, indicating improved consistency in understanding. A p-value of 0.002 and a t-value of -15.800 confirmed the statistical significance of this change. The education covered basic principles of balanced nutrition, proper medication management, and the application of a healthy diet, proving effective in enhancing community knowledge and awareness. This program could serve as a model for similar interventions in other areas, and for sustainability, ongoing monitoring, enhancement of educational materials, and closer collaboration with relevant parties are recommended.